Dokumen kontrak : untuk dismantling and replacement of existing passenger lifts including testing, commissioning and maintenance of twenty three (23) unit new passenger lifts at UTM Johor Bahru, Johor - Universiti Teknologi Malaysia. Pejabat Harta Bina, issuing body; Ryoden Building Machinery Sdn. Bhd. (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
PRZSL